An Analysis of Students’ Errors in Writing Negative Sentences - Rohendi, Mita Nurmayanti; Herlina, Herlina (Universitas Swadaya Gunung Jati, 2015)
This study was carried out to analyze and to classify the kinds and the source of students’ errors in writing negative sentences using simple present tense and simple present continuous tense. The purpose of this study were to describe kinds of the stundents’ errors in writing negative sentences and to find out the source of errors which the students made in writing negative sentences. The method used in this study was descriptive analysis research. Descriptive analysis in form qualitative research design applied in this study was case study. Furthermore, the subject of this study was the students of the seventh grade students of SMPN 13 Cirebon which consisted of 20 students. The data were collected through writing test and interview for students. The result of the analysis of students’ errors process showed that students committed errors into ten kinds of errors are made by students: 1. Omission, 2. Additional, 3. Misformation, 4. Misordering, 5. Omission and misformation, 6. Omission and misordering, 7. Additional and misordering, 8. Additional and misformation, 9. Omission and additional, 10. Misformation and misordering. Based on the finding of analysis, it showed the students made a total of 120 errors in catagory of verb which consist of 21 are omission, 22 are additional, 15 are misformation, 6 are misordering, 8 are omission and misformation, 20 are omission and misordering, 5 are additional and misordering, 10 are additional and mosformation, 10 are omission and additional, and 3 misformation and misordering. These errors were conducted because most of students were still influenced by their mother tongue and their Indonesian logical thinking (interlingual transfer). Besides, errors occurred because students generalized the rule and applied it incompletely (intralingual transfer). To sum up, it showed that the analysis of students’ errors in writing negative sentences using simple present tense and simple present continuous tense is difficult for students.